Cable Aging State Diagnosis Adapted from Frequency-Domain Dielectric Spectroscopy and Polarization–Depolarization Current - Yingqiang Shang; Yang Zhao; Hongquan Ji; Jingyue Ma; Jiren Chen; Ziheng Li; Kejia Wang; Zepeng Lv (Energies, 2025)
Cross-linked polyethylene (XLPE) cables will gradually experience aging under various stresses during long-term operation, which may lead to faults and seriously affect the safe and stable operation of the power system. This article prepares aged cable samples by accelerating the thermal aging of XLPE cables, and combines frequency-domain dielectric spectroscopy (FDS) and the polarization–depolarization current method (PDC) for detection and analysis. By measuring the dielectric loss of aged cables using frequency-domain dielectric spectroscopy, it was found that the dielectric loss value in the low-frequency region significantly increases with aging time, indicating that aging leads to an increase in polarity groups and polarization loss. The high-frequency dielectric loss also significantly increases with the strengthening of dipole polarization. At the same time, using the polarization–depolarization current method to measure the polarization current and depolarization current of cables, it was found that the stable value of polarization current increases with aging time, further verifying the changes in the conductivity and polarization characteristics of insulation materials. Combining the broadband dielectric response characteristics of FDS (0.001 Hz–1 kHz) with the time-domain charge transfer analysis of PDC, the molecular structure degradation (dipole polarization enhancement) and interface defect accumulation (space charge effect) of cable aging are revealed from both frequency- and time-domain perspectives. The experimental results show that the integral value of the low-frequency region of the frequency-domain dielectric spectrum and the stable value of the polarization depolarization current are positively correlated with the aging time, and can make use of effective indicators to evaluate the aging state of XLPE cables.